Evaluation of Common Pediatric Infections: An Annual Survey - Ahmed, Imran; Kazi, Naheed Haroon; Bhand, Sikandar Ali; Memon, Yasirarfat; Khan, Momna; Hussain, Khadim (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pediatric patients are the most frequent population visiting the out patent department with various illnesses round the year. Infections are among the most common reason for illness in this population. Aim: To evaluate the different paediatric infections Study design: Cross-sectional study Place and duration of study: Department of Pediatric, Muhammad Medical College, Mirpur Khas Sindh from 1st January 2018 to 31st December 2018. Methodology: Five hundred and ninety five pediatric patients were enrolled. Results: The male proportion of patients dominated over female proportion with 370(62.18%) and 225(37.82%) respectively. Most cases were of age under 1 year 335(56.30%) followed by age between 1-5 years 134(22.52%) and age group above 5 years was the least affected group 125(21%). Gastroenteritis cases were most common followed by respiratory tract infections and non-infectious diseases. Conclusion: Gastrointestinal infections (gastroenteritis, dysentery and typhoid) were found to be more common in pediatric patients followed by respiratory infections